Circular nucleic acids at the host-virus interface: from immune modulation to therapeutic innovation - Lou, Jiacheng; Liu, Jing; Zhang, Danlu; Hao, Yuchao (Frontiers in Immunology, 2026)
Nucleic acids, long regarded as linear polymers, are now recognized to also exist in circular forms with profound biological significance in both eukaryotic hosts and viruses. This review synthesizes emerging insights into the diverse roles of circular RNAs (circRNAs) and other circular nucleic acids in viral infection and immunity. We first discuss the biogenesis and functions of host-derived circRNAs, emphasizing their complex interplay with innate immunity. These molecules display a striking duality—capable of activating antiviral defenses through pattern recognition receptors such as RIG-I and PKR, yet also exploited by viruses as modulators of immune evasion. We then examine how viral evolution has repeatedly converged on circular architectures, from the minimalist circular RNA genomes of viroids and hepatitis D virus (HDV) to transiently or covalently circularized RNA and DNA viral genomes. A particular focus is placed on hepatitis B virus (HBV), whose covalently closed circular DNA (cccDNA) serves as the persistent nuclear template driving viral replication and chronic infection. We summarize current understanding of cccDNA transcriptional regulation, host factors influencing its activity, and clinical biomarkers such as serum HBV RNA and HBcrAg that reflect cccDNA dynamics. Finally, we highlight the biotechnological applications of circularity, including circRNA-based vaccines offering superior stability and durable antigen expression, and circular nucleic acid probes for viral diagnostics. Collectively, this review positions circular nucleic acids as central players at the host–virus interface, shaping immunity, persistence, and the next generation of antiviral strategies.